Efektifitas Penambahan Source to Image Distance (SID) terhadap Penurunan Dosis Radiasi pada Pemeriksaan Radiografi Cranium - Angga Yosainto Bequet; Panji Wibowo Nurcahyo; Akhmad Haris Sulistiyadi (Poltekkes Kemenkes Semarang, 2022)
Background: Cranial radiographs are routinely made in 2 projections, namely Antero Posterior (AP) and Lateral with a minimum distance of 100 cm from the radiation source to the image receptor. In addition, it has been shown that increasing the SID from 40 to 48 inches reduces the skin dose even when the requirement for an increase in mAs is considered. A 44-inch or 48-inch SID is recommended where departmental equipment and protocols allow. This study aims to determine the effectiveness of the addition of SID to decrease the radiation dose on cranium radiographs.Methods: This type of research is a pre-experimental quantitative. The study was conducted at the radiology laboratory of Diploma Three Program of Radiology Purwokerto, Semarang Health Politechnic of Ministry of Health. The research subject is a Radiographic Xray Cranial Phantom. At the time of exposure, the radiation dose was measured and the resulting image was measured CNR value.Results: The results of radiation dose measurements at each SID setting for AP cranium radiographs are shown in the table above. setting SID 100 cm produces a radiation dose of 5.58 mSv, SID 110 cm produces a radiation dose of 5.16 mSv, SID 120 cm produces a radiation dose of 5.02 mSv, SID 130 cm produces a radiation dose of 4.84 mSv, SID 140 cm produces a radiation dose of 4.64 mSv and SID 150 cm produces a radiation dose of 4.36 mSv. There are differences in radiation dose values between SID settings of 100 cm, 110 cm, 120 cm, 130 cm, 140 cm and 150 cm with a statistical test p-value 0.001. The results of statistical tests on the Contrast to Noise Ratio value on changes in the SID value of the AP cranium radiography examination showed no significant difference. The p-value of the statistical test is 0.274 which means there is no difference in the CNR value between the SID settings of 100 cm, 110 cm, 120 cm, 130 cm, 140 cm and 150 cm.Conclusions: An increase in SID causes a decrease in radiation dose. The increase in SID did not cause a significant difference to the quality of the Contrast to Noise Ratio on the AP cranium radiograph image.